Economics of Angora rabbit farming in hills - TRIPATHI, R S; DEV, CHANDRA; SHARMA, M L (The Indian Journal of Animal Sciences, 2013)
Angora rabbit farming is an economically viable add profitable enterprise for the hill. Tpta; costÂ  of rabbit fanning was Rs 14 656/farm an annurn-77% was on variable and 23% on fixed costs. The gross and net returns were Rs 39836 and Rs 25 18l/farm a year. The return over per rupee investment was Rs 2.72. Concentrates and filted cost made positive and significant impact on the returns of meal and wool + meat (pooled) production. The break-even size of herd was 20 rabbits for the production of wool and 2 rabbits for meat and wool + meat (pooled) per farm.